INCIDENCE OF GASTROINTESTINAL NEMATODES IN SMALL RUMINANTS, EFFECT ON GROWTH RATE AND THEIR SENSITIVITY TO DIFFERENT ANTHELMINTICS (The Research of Medical Science Review, 2025)
The worm infestation has a key impact on the health status and livestock production system, especially small ruminants that are raised on grazing system. In this contribution, we have studied the prevalence of gastrointestinal nematodes and comparative efficacy of most common used anthelmintics (i.e., Levamisole, Oxfendazole, and Ivermectin) in small ruminants in tribal areas of Pakistan. The overall worm prevalence was 74%. Among various types of nematodes, Trichuris Ovis was the most prevalent followed by Heamonchus contortus and Trichostrongylus. Also, the infestation was higher in young and female as compared to adult and male animals, respectively. Furthermore, the efficacy of selected anthelmintics was evaluated based on the reduction of eggs per gram (EPG) of the fecal sample on day 14th, 21st, 28th post-medication. The efficacy of Levamisole was highest (87.74%), followed by Oxfendazole (84.97%) and Ivermectin (82.65%). Likewise, the growth rate was also found higher in the Levamisole treatment group (i.e., 105.71 g/day), followed by Oxfendazole (82.85 g/day) and Ivermectin (70 g/day). Our results not only demonstrate the prevalence of gastrointestinal parasites in small ruminants but also their sensitivity to anthelmintics in vogue that may help in the improvement of the local livestock production system.